PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP SEMANGAT KERJA KARYAWAN PADA DEPARTEMEN TEAM SUPPORT PT GRAHA SARANA DUTA AREA 2 DI BUMI SERPONG DAMAI - Shafira, Rahma; Suprapti, Endang (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work discipline and physical work environment on employees' work enthusiasm at PT Graha Sarana Duta Area 2 in Bumi Serpong Damai, both partially and simultaneously. This study utilized the quantitative associative method. The sampling technique employed a saturated sample of 55 respondents. Data analysis techniques included data instrument test, classical assumption test, simple linear regression, multiple linear regression, correlation coefficient, and determination coefficient. Hypothesis testing used t-test and F-test. The results show that work discipline partially affects employees' work enthusiasm with a simple linear regression equation of Y = 7.558 + 0.881X1. The correlation coefficient value of 0.941 indicates a very strong relationship, and the determination coefficient of 0.886 indicates that work enthusiasm is influenced by work discipline by 88.6%, while the remaining 11.4% is influenced by other factors not studied in this research. This is evidenced by the t-test result where t-value > t-table (11.130 > 2.006) and further supported by a significance value < 0.05 (0.000 < 0.05). Physical work environment partially positively influences employees' work enthusiasm, as shown by the simple linear regression equation Y = 11.608 + 0.810X2. The correlation coefficient value of 0.861 indicates a very strong relationship, and the determination coefficient of 0.741 indicates that work enthusiasm is influenced by the physical work environment by 74.1%, while the remaining 25.9% is influenced by other factors not studied in this research. This is evidenced by the t-test result where t-value > t-table (5.064 > 2.006) and further supported by a significance value < 0.05 (0.000 < 0.05). The research findings indicate that work discipline and physical work environment simultaneously influence employees' work enthusiasm, as shown by the multiple linear regression equation Y = 5.645 + 0.648X1 + 0.297X2. The correlation coefficient value of 0.961 indicates a very strong relationship, and the determination coefficient of 0.924 indicates that work enthusiasm is influenced by work discipline and physical work environment by 92.4%, while the remaining 7.6% is influenced by other unexamined factors. This is evidenced by the F-test result where F-value > F-table (314.004 > 2.78) and further supported by a significance value < 0.05 (0.000 < 0.05). Therefore, it is proven that Ho is rejected and Ha is accepted.